Optimizing Teacher Performance Human Resources in Facing the Digital Era - Romadhoni, Kunni Faizah; Munjiyah, Sab'atun; Retnani, Dwi (Proceedings Series on Social Sciences & Humanities, 2025)
The development of digital technology has brought major changes in the world of education, requiring teachers to adopt more innovative and technology-based teaching methods. Teachers are required to have adequate digital competence in order to be able to face the challenges of the digital era. Therefore, optimizing human resources (HR) is very important to improve teacher performance. This study aims to analyze HR optimization strategies to improve teacher performance in facing the digital era. The method used is a literature review by reviewing various relevant previous studies related to improving teacher competence in the digital era. The results of the study show that the development of technological competence, pedagogical innovation, and ongoing training are effective strategic steps in improving teacher performance. In addition, institutional support in the form of providing digital infrastructure and strengthening education policies are key factors in the HR optimization process. The synergy between strengthening teacher competence and support for the education system can create a learning ecosystem that is adaptive to the development of digital technology. The recommendations of this study emphasize the importance of cross-sector collaboration in providing technology-based training and ongoing teacher professional development to strengthen the quality of education in the digital era.